2016
DOI: 10.18517/ijaseit.6.5.957
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Surface Finish by Multiple Piezoelectric Transducers in Fused Deposition Modelling

Abstract: Additive Manufacturing (AM) which embrace as a new range technology of creating and producing end user parts in term of adding material layer by layer to create solid objects from 3D CAD data. AM in particular Fused Deposition Modelling (FDM) used (ABS) thermoplastic have shown the most popular among the industry as its technology can print complex geometrical part without human intervention and tools. However, FDM fierce enemy whereas the common problem of stair-stepping, which means that seam lines appear be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…We call this technique vibration-assisted FDM (VA-FDM). Our approach is different than the recently reported application of ultrasonic vibrations on print bed, which was focused on the surface finish of FDMed polymers (Mohamed et al , 2016). We also provided a detailed Weibull analysis of the mechanical properties of FDMed SCFR-ABS, which is currently missing in the literature.…”
Section: Introductionmentioning
confidence: 87%
“…We call this technique vibration-assisted FDM (VA-FDM). Our approach is different than the recently reported application of ultrasonic vibrations on print bed, which was focused on the surface finish of FDMed polymers (Mohamed et al , 2016). We also provided a detailed Weibull analysis of the mechanical properties of FDMed SCFR-ABS, which is currently missing in the literature.…”
Section: Introductionmentioning
confidence: 87%
“…Up to now, there have only been few experiments that have been conducted to investigate the effect of ultrasound on printed polymers and composites. In a few experiments, it has been identified that, by supplying ultrasonic vibration during printing, the surface quality of the final product can be improved while reducing the staircase effect and layer thickness [ 253 , 254 ]. Maidin et al [ 255 ] performed an experiment to identify the impact of ultrasound vibration on the ABS polymer print by accompanying it with an ultrasound frequency of 11 kHz, 16 kHz and 21 kHz.…”
Section: Treatment Methods To Overcome or Minimize The Defects In mentioning
confidence: 99%
“…In this method, ultrasonic vibration is supplied during part printing due to which staircase effect and layer thickness gets reduced and surface quality of end product gets improved. 116,117 In one of the study, 3D printing of ABS polymer was accompanied by 11 kHz, 16 kHz and 21 kHz ultrasonic vibration using piezoelectric transducer. It was observed that at 21 kHz frequency of vibration, 3D printed part had achieved remarkable surface finish.…”
Section: Ultrasound Treatmentmentioning
confidence: 99%